Effective Communication in Advertising - Ervin Muhammad Dermawan; Cecep Safa'atul Barkah (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2022)
This study aims to find out how important effective communication is in messaging in advertising and how to use effective communication for advertising delivery. The method used in this study is a literature review. The results obtained in this study are that advertising is a communication used to convey messages to many people. The importance of effective communication in the delivery of the message will achieve the purpose of the advertisement itself. The purpose of advertising is to change or influence the attitudes of the audience, in this case, of course, the attitudes of consumers. The effectiveness of advertising can be seen from brand recognition, advertising is remembered, and the advertising message is understood. The higher the level at which the brand is known, the advertisement is remembered, and the advertising message is understood, the more effective it will be in conveying its purpose. In addition, the use of communication is effective in the delivery of messages in advertising by using easy-to-understand word selection, attractive design, creative ideas, and big ideas that can get reactions.